Analysis of the Relationship of Service Quality, Motivation and Destination Image to Destination Loyalty: A Case Study of Wonorejo Mangrove Ecotourism in Surabaya, East Java - Anggi Novita Dewi; Zainal Abidin (Journal of Aquaculture and Fish Health, 2021)
Surabaya as the capital of East Java Province has a tourism attraction based on mangrove ecosystems namely Wonorejo Mangrove Ecotourism. Interest to the growth of loyalty to the destination depends on service quality, motivation, and destination image. Service quality as the heart of marketing and one of the concepts of loyalty success determines the sustainability of a tourist destination in the future. In addition, motivation is also considered as the main driver for traveling. However, this depends on destination image in the minds of tourists. The purpose of this study was to analyze the direct and indirect relationship between service quality and motivation towards destination loyalty, which is mediated by destination image. From 276 online and offline questionnaires distributed to local tourists who visited or visited the Wonorejo Mangrove Ecotourism in the past years, 182 questionnaires were filled in completely. Data analysis used WarpPLS to examine the relationship of influence between variables. The results showed that service quality and motivation had a positive and significant effect on destination loyalty directly or mediated by destination image. Destination loyalty can be effectively increased by encouraging visitor motivation supported by an increase in destination image because the value of the total influence was at the largest of 0.443.